Estimation of the genetic diversity of jabuticaba trees and association among fruit characters - Rufini, José Carlos Moraes; Fagundes, Miriã Cristina Pereira; Magalhães, Deniete Soares; Albuquerque, Alejandra Semiramis; Ramos, Martha Cristina Pereira; Pereira, Ana Clara Pimenta (Comunicata Scientiae, 2020)
The aim of this study was to evaluate the genetic dissimilarity of different jabuticaba tree accessions from Prudente de Moraes, Minas Gerais State, Brazil, based on fruit characters. The genetic diversity study was carried out based on characters evaluated in fruits, and with the elimination of redundant descriptors, nine characters were selected to estimate genetic divergence and perform clustering. The Standardized Mean Euclidian Distance was used as dissimilarity measure. The clustering methods used were Tocher and the nearest neighbor. Correlation analysis among characters was performed by Pearson correlation (p> 0.05). Accessions 4, 5, 7 and 12 have potential for in improvement programs aiming for productivity. The character that contributed most to the genetic diversity of the accessions were the soluble solids important for the processing industry and for fresh consumption. Genotypes showed variability for most characters analyzed showing the possibility of selection and identification of parents that will be used in future crossings.